PROBLEMS AND SOLUTIONS IN WIND ENERGY: OVERCOMING CHALLENGES FOR A SUSTAINABLE FUTURE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Wind energy is a key component of the global shift toward renewable energy. However, despite its potential, the widespread adoption of wind power faces several challenges, including intermittency, land use concerns, and environmental impacts. This article examines the key problems hindering the growth of wind energy and discusses potential solutions to overcome these obstacles. The findings reveal that technological innovations, policy support, and improved grid integration can address many of the current limitations, positioning wind energy as a crucial contributor to a sustainable energy future.